A radiation ulcer that required partial lung resection and recurred in a small residual area of ectopic calcification. (August 2021) - Nakanishi, Takashi; Kuwahara, Masamitsu; Sasaki, Chikako; Ando, Junji; Harada, Masayuki; Takeuchi, Mika
Abstract: Introduction and importance: Surgery for chest radiation ulcers must involve appropriate wide margins, but it is not usually possible to remove all radiation-damaged tissue. Therefore, it is difficult to determine how extensive such surgery should be. There have not been any reports about the recurrence of such ulcers years after surgery. In addition, how ectopic calcification should be treated and the need for partial lung resection in such cases have not been fully elucidated. We report the case of a patient who had a large severe radiation ulcer. Case presentation: A 46-year-old patient underwent cancer resection and received postoperative radiotherapy. Seventeen years later, a chest ulcer developed. Computed tomography showed a depression of the lung parenchyma, which exhibited old radiation pneumonitis, and pathological fractures of the ribs around the ulcer. We excised a region of skin that exhibited a clear change in color together with an additional 1 cm around this area including 4 ribs and grossly calcified area. The lung was partially resected because of strong adhesion, and the chest wall was reconstructed. Two small calcifications remained and which required additional surgery several years later. Clinical discussion: Since multiple surgeries were required, we consider that more generous resection margins were necessary from the beginning. Conclusion: In such cases, it might be necessary to perform more extensive surgery that includes asymptomatic calcified areas. Highlights: Surgery for chest radiation ulcers, it is still difficult to determine how extensive should be. Our case required partial lung resection and recurred in a small residual area of ectopic calcification. Since multiple surgeries were required, more generous resection margins were necessary from the beginning.